Interpreting Japanese society : anthropological approaches - Hendry, Joy. (London ; New York : Routledge, 1998)
First published in 1986, Interpreting Japanese Society became something of a classic in the field. In this newly revised and updated edition, the value of anthropological approaches to help understand an ancient and complex nation is clearly demonstrated. While living and working in Japan the contributors have studied important areas of society. Religion, ritual, leisure, family and social relations are covered as are Japanese preconceptions of time and space - often so different from Western concepts. This new edition of Interpreting Japanese Society shows what an impo.
Introduction : the contribution of social anthropology to Japanese studies / Joy Hendry -- Spatial characterization of human temporality in the Ryūkyūs / Patrick Beillevaire -- The Pythagorean view of time and space in Japan / Thomas Crump -- The question of space : from Heidegger to Watsuji / Augustin Berque -- Contested identities and models of action in Japanese discourses of place-making : an interpretive study / Eyal Ben-Ari -- Time, space and person in Japanese relationships / Jane M. Bachnik -- Is the ie disappearing in rural Japan? : the impact of tourism on a traditional Japanese village / Okpyo Moon -- Death rites in Japan in the twentieth century / Jan van Bremen -- A child in time : changing adoption and fostering in Japan / Roger Goodman -- Gods, ancestors and mediators : a cosmology from the south-western archipelago of Japan / Teigo Yoshida -- The importance of the left hand in two types of ritual activity in Japanese villages / Kazuto Matsunaga -- "Years of calamity" : yakudoshi observances in urban Japan / David C. Lewis -- Redefining Kuzaki : ritual, belief and chō boundaries / D.P. Martinez -- Science and religious movements in Japan : hi-tech healers and computerized cults / Mary Picone -- Sakariba : zone of "evaporation" between work and home? / Sepp Linhart -- One over the seven : sake drinking in a Japanese pottery community / Brian Moeran -- Models of performance : space, time and social organization in Japanese dance / James Valentine.
Includes bibliographical references and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Japan -- Civilization -- 1945-; Japan -- Social conditions -- 1945-; Japon -- Civilisation -- 1945-; Japon -- Conditions sociales -- 1945-; HISTORY; Civilization; Social conditions; Japan; Since 1945